Effects of hypertension on maternal adaptations to pregnancy: experimental study onspontaneously hypertensive rats - Peraçoli, José Carlos; Rudge, Marilza Vieira Cunha; Sartori, Maria Salete; Franco, Roberto Jorge da Silva (São Paulo Medical Journal, 2001)
CONTEXT: Animal models for essential hypertension have been used for understanding the human pathological conditions observed in pregnant hypertensive women. OBJECTIVE: To study the possible effects of pregnancy on hypertension and of hypertension on pregnancy in spontaneously hypertensive rats (SHR), and in their normotensive Wistar-Kyoto (WKY) counterparts. TYPE OF STUDY: Comparative study using laboratory animals. SETTING: Animal Research Laboratory of Clinical Medicine at the Medical School of Botucatu, São Paulo State University, Brazil. SAMPLE: Ten to twelve-week-old virgin female normotensive Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHR). The animals were separated into four groups: 15 pregnant spontaneously hypertensive rats (SHR-P), 10 non-pregnant spontaneously hypertensive rats (SHR-NP), 15 pregnant normotensive rats (WKY-P), and 10 non-pregnant normotensive rats (WKY-NP). MAIN MEASUREMENTS: The blood pressure was evaluated by the tail cuff method, in rats either with or without prior training for the handling necessary for tail cuff measurements. The maternal volemia expansion was indirectly evaluated by weight gain, and by systemic parameters as hematocrit, hemoglobin, total protein, albumin and sodium retention. The perinatal outcome of pregnancy was evaluated by analysis of resorptions, litter size, rate of low weight and number of stillbirths. RESULTS: The late fall in blood pressure in the pregnant SHR strain and in the normotensive WKY strain can only be detected in rats previously trained to accept the handling necessary for the tail cuff measurement. During pregnancy the body weight gain was significantly higher in WKY than in SHR rats. Systemic parameters were significantly lower in pregnant WKY rats than in nonpregnant WKY rats, while no differences were observed between pregnant and non-pregnant SHR groups. In pregnant WKY rats the sodium retention was higher from the 13th day onwards, while in SHR rats this occurred only on the 21st day. The characteristics of reproductive function such as number and weight of fetus, perinatal mortality and the resorption rate were significantly affected in the SHR strain. CONCLUSION: The SHR strain may be considered as a model for chronic hypovolemic maternal hypertension, with the fetal growth retardation being determined by this hypovolemic state.